Suzuki and Stille Cross-Coupling Reactions from β-Iodovinylphosphonate: Stereoselective Access to Various Substituted Vinylphosphonates - Thiery, Emilie; Abarbri, Mohamed (Synthesis, 2014)
Stereoselective synthesis of β-arylvinyl, dienyl, and enynylphosphonates was achieved from diethyl 2-iodovinylphosphonate via Suzuki or Stille cross-coupling reactions in good yields.
Keywords: cross-coupling; stereoselective; arylvinylphosphonates; dienylphosphonates; enynylphosphonates